-2x+5x-45=12

Simple and best practice solution for -2x+5x-45=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+5x-45=12 equation:


Simplifying
-2x + 5x + -45 = 12

Reorder the terms:
-45 + -2x + 5x = 12

Combine like terms: -2x + 5x = 3x
-45 + 3x = 12

Solving
-45 + 3x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + 3x = 12 + 45

Combine like terms: -45 + 45 = 0
0 + 3x = 12 + 45
3x = 12 + 45

Combine like terms: 12 + 45 = 57
3x = 57

Divide each side by '3'.
x = 19

Simplifying
x = 19

See similar equations:

| 4x-2(x-2)=-8+5x-6 | | -7+g+1-6g=0 | | 8-3x=7x-52 | | 10(x+4)-6x=12x-8 | | Xy-2x=4+3x | | 6p-2/7=5p+7-8 | | 2(3x+3)=11x+4-5x+2 | | 8n-7=5n | | -2-10x=18 | | -2(6-10x)=20x-60 | | 5(6x-5)-3(3x-18)=4(5x+1)-1 | | 12x+6x-192=60 | | 25t=5(t+1) | | 15(x-2)=5(x-6) | | 4z-8=5z-6 | | 2/5(10x-25)=4 | | v+4/12=5/8 | | 2x^2+8=x^2+40 | | 1/9(9y+36)-6=-1/3(6y-21) | | 19=-8+3x | | -4x+4=2x-26 | | 2(-18)+8(2)=4 | | 18=9d+7d | | 8(x-5)=21(3x-8) | | (-13x2/3)X15 | | 1/9(9y+36)-6 | | -95=10x-5 | | 31-(2c+3)=2(c+4)+c | | x-c/2+d | | -32=-20+p | | 4=16-4x | | 4y+1=-2y-5 |

Equations solver categories